Pengaruh Asset Growth, Dividend Payout Ratio (DPR) dan Price Earning Ratio (PER) terhadap Return Saham Pada LQ 45 Di BEI Periode 2015 - 2017 - Natalia Ratna Ningrum (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2019)
This research is to know about the Asset Growth, Dividend Payout Ratio, and Price Earning Ratio affects to Return Saham at LQ 45 in BEI Period 2015 - 2017. The objects in this research is companies that registered in LQ 45 group in BEI period 2015 - 2017. I’m using purposive sampling as the sampling technique, and regresi with SPSS for Windows program as the analyzing technique. The research result shows that the first Hypothesis is testing about the effect between Asset Growth to Stock Return and resulted value p-value 0,737 > 0,05 (no effect), so it can be concluded as H01 accepted (H1 rejected). So the variable of Asset Growth is no affects Stock Return, and the second Hypothesis is testing about the effect of Dividend Payout Ratio to Stock Return and resulted the p-value 0,027 < 0,05 (significant), so it can be concluded as H02 rejected (H2 accepted). So the variable of Dividend Payout Ratio is significantly affects Stock Return, and the third Hypothesis, Hypothesis is testing about the effect of Price Earning Ratio to Stock Return and resulted the p-value 0,122 < 0,05 (no effect), so it can be concluded as H03 accepted (H3 rejected). So the variable of Price Earning Ratio is no affects Stock Return, and by testing F simultaneously resulted value the significance level is 0,048. Because the significance level 0,048 < 0,05, so the zero hypothesis (Ho) is rejected. It means that Asset Growth, Dividend Payout Ratio and Price Earning Ratio affects significantly to Stock Return.